Government Support to Agricultural Insurance : Challenges and Options for Developing Countries - Mahul, Olivier; Stutley, Charles J. (World Bank, 2012)
Governments in developing countries have been increasingly involved in the support of commercial agricultural (crop and livestock) insurance programs in recent years. A striking example is China, where, with support (and premium subsidies) from the central and provincial governments, the agricultural insurance market grew dramatically to become the second largest market in the world (after the United States) in 2008. In India and Mexico, weather-based crop insurance has been developed on a large scale to protect farmers against the vagaries of the weather. Many other countries have investigated the feasibility of agricultural insurance, and some have implemented pilot programs. This book aims to inform and update public and private decision makers involved in promoting agricultural insurance about recent developments in agriculture insurance. The literature is heavily biased toward the practice and experience of a few very large public-private programs in Northern America and Europe, which are driven by large public financial subsidies. This book provides decision makers with a framework for developing agricultural insurance. It is based on an analytical review of the rationale for public intervention in agricultural insurance and a detailed comparative analysis of crop and livestock insurance programs provided with and without government support in more than 65 developed and developing countries. The comparative analysis is based on a survey conducted by the World Bank's agricultural insurance team in 2008. Drawing on the survey results, the book identifies some key roles governments can play to support the development of sustainable, affordable, and cost-effective agricultural insurance programs.